Social Work Studies at a Haredi Women's College: Difficulties and Dilemmas. - Baum, Nehami; Schwartz, Chaya; Yedidia, Tova; Aran, Ofra (Social Work Education, 2014)
This paper examines the challenges faced by female Ultra-Orthodox students in a social work program designed for the Ultra-Orthodox community in Israel. Findings were obtained from four focus groups with a total of 32 students. The participants reported being exposed to contents that were inconsistent with the perspectives of their community, fieldwork expectations and requirements that violated strict rules of gender separation, and inconvenient scheduling of exams and field trips that did not take their religious observances into consideration. Despite the considerable distress that these matters caused, most of the students made determined efforts to cope, to learn the course material, to carry out their fieldwork assignments, and to reconcile the discrepancies between some of the contents they learned and behaviors that were expected of them and their deeply held values and ways. Implications of the findings are discussed and recommendations made.